THE EFFECTIVENESS OF PROVIDING RACED CHICKEN EGGS ON THE NUTRITION FOR PREGNANT WOMEN IN CHRONIC ENERGY DEFICIENCY IN KENDARI CITY, SULAWESI, TENGGARA: Raced Chicken Eggs on theNutrition - Aisa, Sitti; Sunarsih; Nurmiaty (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background: Chronic Energy Deficiency (CED) of energy is a problem that is often encountered in pregnant women, this often occurs due to malnutrition in the long term, especially those related to carbohydrates and fats that are not consumed. Research purposes; For the effect of eating one egg a day on the nutritional status of pregnant women in CED in Kendari City, Southeast Sulawesi Province in 2020.  Methods: Using a quasi-experimental design, the total sample was 36 CED pregnant women, in the working area of ??Primary health care Nambo and Primary health care Abeli. Intervention Egg delivery was carried out for 8 weeks, measured LBW and BW every 2 weeks, measurements were carried out 5 times, namely before the intervention, after weeks 2, 4, 6 and 8. Data analysis used independent t test, paired test and oneway statistical test. anova.     Result: Using the independent t test, the results were there were no differences between the body weight (BW) and Upper Arm Circumference (UAC) interventions and the group before the study. Furthermore, the paired test results obtained differences in weight and LBW before and after offering eggs to the intervention group. There were differences in BW and UAC after offering eggs to The results of the independent t test were obtained. There were differences in weight and UAC after offering eggs in the intervention group and the control group. The results of the analysis with the one-way aova test showed that the effective time of offering boiled eggs to increase body weight and UAC was the eighth week  Conclusion: There was no difference in weight and UAC in the intervention group and control group before the study, but there were differences in weight and LBW before and after egg administration in the intervention and control groups